The finds from the Iron Age settlement (Scottish Historical and Archaeological Internet Reports, 2007)
Specialist reports on pottery, coarse stone, copper alloy, iron, slag, Roman glass, oil shale and cannel coal, slag and antler. There is also a general discussion of the artefact assemblage as a whole.